PID digital controller for DC motor speed using MC68HC11 microcontroller - Peterus, Sharon (2008)
The proportional-integral-derivative (PID) controllers are widely used in many industrial control systems for several decades since Ziegler and Nichols proposed their first PID tuning method. This is because the PID controller structure is simple and its principle is easier to understand than most other advanced controllers. On the other hand, the general performance of PID controller is satisfactory in many applications. For these reasons, the majority of the controllers used in industry are of PI/PID type. PID controllers are widely used for process control applications requiring very precise and accurate control. The purpose of the motor speed controller is to take a signal representing the demanded speed, and to drive a motor at that speed. The controller does not actually measure the speed of the motor. Thus, it is called an Open Loop Speed Controller. Motors come in a variety of forms, and the speed controller's motor drive output will be different dependent on these forms. The speed controller presented here is designed to drive special dc motor which is not easily available anywhere in store, thus it is a good example to be used due to the special characteristics and parameters. Matlab Simulink® is an important tool used it this project, from designing the mathematical model of the dc motor, obtaining the transfer function, and designing the PID controller using both model and programming using m-files. The transfer function will be linearized and used for tuning the gain of PID controller like KP, KI, and KD. Simulink is chosen to simulate the performance of the control system.